Pemanfaatan E-Learning Media untuk Pembelajaran Bahasa Inggris di Sekolah Dasar - Dewi Syafitri; Ani Fiani; Nadila Fitri; Dwi Maulianto (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The use of E-learning media in learning English in elementary schools, especially SD Negeri 36 Lubuklinggau City is carried out as a strategic step to maximize the quality of education. With the support of appropriate infrastructure and training, it is hoped that this community service will make a significant contribution in improving the teaching competence of English teachers so that they can have a positive impact on their students and expand access to quality education at the elementary level. The implementation methods used in this service are: a) preparation stage; b) implementation stage which includes: socialization, discussion and practice; and c) Evaluation. The results of the implementation of this activity show 1) the implementation of the coordination between the PKM UNPARI Lubuklinggau team and SD Negeri 36 Lubuklinggau City, so that the activity took place safely and smoothly, 2) the socialization of the use of learning media such as YouTube Video, British Council, and Kahoot, 3) the teacher council was enthusiastic in supporting the socialization activities, and 4) The obstacles faced are related to the limited time for carrying out community service activities. In general, this activity is useful for helping class teachers who teach English at the elementary school level.